ЗНАЧЕНИЕ РОЛИ ИСКУССТВА В СОВРЕМЕННОМ ПОНИМАНИИ СОДЕРЖАНИЯ ОБРАЗОВАНИЯ - Уразимова, Т.В. (SCIENCE and SOCIETY, 2017)
The article is devoted to the modern content and role of the educational process, since modern society has increased attention to the problem of formation of a fully developed , spiritually rich and creative personality. Human personality and his spiritual and moral character are formed primarily in the process of education. Not the last role is played here by aesthetic education, contributing to enhance the development of philosophy , intellectual and creative potential of the individual. Therefore, the process of education should be based on creating conditions for education of creative personality, ready for dialogue , collaboration and co-creation in various spheres of life.